Growth and Interdependence - Ventura, J. (Quarterly Journal of Economics, 1997)
Two of the most interesting facts of the postwar international growth experience are (1) the conditional convergence finding that, after controlling for measures of education and government policies, poor countries tend to grow faster than rich ones; and (2) a small group of export-oriented economies in East Asia have been able to grow at rates that are so high that they defy historical comparisons. This paper shows that it is possible to explain these facts by combining a weak form of the factor-price-equalization theorem of international trade with the Ramsey model of economic growth.